9x-(3x-7)=25

Simple and best practice solution for 9x-(3x-7)=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-(3x-7)=25 equation:


Simplifying
9x + -1(3x + -7) = 25

Reorder the terms:
9x + -1(-7 + 3x) = 25
9x + (-7 * -1 + 3x * -1) = 25
9x + (7 + -3x) = 25

Reorder the terms:
7 + 9x + -3x = 25

Combine like terms: 9x + -3x = 6x
7 + 6x = 25

Solving
7 + 6x = 25

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 6x = 25 + -7

Combine like terms: 7 + -7 = 0
0 + 6x = 25 + -7
6x = 25 + -7

Combine like terms: 25 + -7 = 18
6x = 18

Divide each side by '6'.
x = 3

Simplifying
x = 3

See similar equations:

| 13-16g+4g=25 | | 46=2(12)+2(b) | | a-7=-26 | | (x-5)(x^2-11x+28)=0 | | 3y-8x=17 | | 113=276-q | | 5e^8t=6e^7t | | 8-3(x+1)=20 | | 15x+x-12=63 | | 2+x+19=2x+33 | | 2x+5(x-4)=8 | | 10b+10+2b=-10+8b | | -6x-x=20 | | 19x-(8x-4)=92 | | (X+78)x+41=95 | | -2=b-11 | | 126=-7(-5a-3) | | 3(x+2)=2(2+x) | | 2(-6-5x)=68 | | 5x+6-x=7+5x-6 | | (X+78)x+42=95 | | 3x+7y=62 | | 3(x+40)= | | (5x-4)(5x+4)=80 | | b-4+2b=27 | | 5-3x=10x-35+2 | | -7(c+372)+620=-185 | | 4(5z+1)-6=178 | | 2(n+7)=5n+8 | | b-4+26=27 | | (X+41)x+78=95 | | 53=29-4(x-4) |

Equations solver categories